Hepatic Histologic Changes in Patients with Chronic Hepatitis B Virus Infection with High DNA Level and Normal or Minimally Elevated Alanine Aminotransferase (Faridpur Medical College Journal, 2016)
Hepatitis B Virus (HBV) infection can causes spectrum of diseases ranging from clinically asymptomatic state to the development of cirrhosis and hepatocellular carcinoma (HCC). There is ongoing debate in the management of asymptomatic patients with chronic hepatitis B virus (CHBV) infection with high DNA and normal ALT level. It has been recently shown that a significant proportion of patients with CHBV infection with high DNA and normal ALT level have significant histological abnormality. So this study was aimed to see the histological changes in patients with CHBV infection with high DNA and ALT level